TECHNICAL EFFICIENCY ASSESSMENT OF PUBLIC HEALTH CENTERS IN MATARAM CITY: A DEA APPROACH (2021-2023) - Juliana, Nadya Eka; Muhsyaf, Saipul Arni (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study examines the efficiency of public health centers (PHCs) in Mataram City between 2021 and 2023 using Data Envelopment Analysis (DEA). An output-oriented Constant Returns to Scale (CRS) model was applied to 11 PHCs—five inpatient and six non-inpatient—to assess how efficiently they utilize inputs such as health workers, support staff, operational budgets, population served, and bed capacity to deliver outputs like outpatient visits, immunization coverage, family planning services, and inpatient admissions. Efficiency scores were calculated using DEAP 2.1 software. The findings reveal that several PHCs, including Cakranegara, Tanjung Karang, Ampenan, and Karang Taliwang, consistently achieved optimal efficiency (score: 1.000), while others, such as Selaparang and Karang Pule, showed room for improvement. These disparities indicate opportunities for targeted operational enhancements and better resource reallocation. The study provides actionable benchmarks for underperforming PHCs, supporting data-driven decisions and the implementation of performance-based budgeting, particularly in the context of public sector accountability and healthcare optimization.